2001
DOI: 10.1002/cm.1024
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of elongation factor 1α from Zea mays (ZmEF‐1α) with F‐actin and interplay with the maize actin severing protein, ZmADF3

Abstract: EF-1alpha is an abundant eukaryotic protein whose principle function appears to be to bind aminoacyl-tRNA to the ribosome. However, it is also known that EF-1alpha from other sources binds both microtubules and microfilaments. We report the expression of Zea mays EF-1alpha (ZmEF-1alpha) in bacteria and that this protein has similar actin-binding properties as other EF-1alpha members. ZmEF-1alpha bundles actin filaments at low pH (6.5) and inhibits the addition of monomer at both filament ends, possibly as a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…Gelsolin-severed short actin filaments (up to 1:50 molar ratios of gelsolin and actin) were efficiently bundled by UNC-87 (our unpublished data), suggesting that the inhibitory effect of UNC-60B is not simply due to shortening of the filaments. This antagonistic effect contrasts the previously reported synergistic effects on actin bundling between ADF/cofilin and ␣-actinin (Maciver et al, 1991a) or elongation factor 1␣ (Gungabissoon et al, 2001). …”
Section: Unc-87contrasting
confidence: 98%
“…Gelsolin-severed short actin filaments (up to 1:50 molar ratios of gelsolin and actin) were efficiently bundled by UNC-87 (our unpublished data), suggesting that the inhibitory effect of UNC-60B is not simply due to shortening of the filaments. This antagonistic effect contrasts the previously reported synergistic effects on actin bundling between ADF/cofilin and ␣-actinin (Maciver et al, 1991a) or elongation factor 1␣ (Gungabissoon et al, 2001). …”
Section: Unc-87contrasting
confidence: 98%
“…The regulation of fimbrin binding activity to F-actin is still unclear, but its activity is [Ca 21 ] insensitive (Kovar et al, 2000). Elongation factor-1a is a dual-function protein with aminoacyl tRNA binding as well as actin-binding and -bundling activities (Gungabissoon et al, 2001). In this study, we demonstrated that pH and [Ca 21 ] can simultaneously regulate the F-actin binding of LlLIM1.…”
mentioning
confidence: 76%
“…Weak severing activity is known for non-plant ADF/cofilin proteins (71). Severing has never been demonstrated directly for a plant ADF, although it is often inferred from depolymerization and polymerization assays (72,73). The relative contribution of severing versus enhancing the off-rate at pointed ends to ADF/ cofilin depolymerizing activity remains controversial (74 -76).…”
Section: Discussionmentioning
confidence: 99%